El derecho a la vivienda digna como un derecho social y programático. Una de las reformas constitucionales pendientes en el Perú - Roel Alva, Luis Andrés (2023)
The objective of this study is to analyze the constitutional reform proposal on the right to decent housing, presented by the author before the Congress of the Republic of Peru. This proposal was materialized through Bill No. 05839/2020-CR, which seeks to incorporate the Fundamental Right to Decent Housing in the Political Constitution of Peru. The intention of this proposal is to include numeral 25 in Article 2° of the Peruvian Constitution, in order to integrate the fundamental right to decent and adequate housing in the set of rights explicitly recognized by the Peruvian Magna Carta, so that the State can implement the necessary actions and measures to guarantee its access. Thus, this right acquires greater relevance in the context of the Covid-19 pandemic. Indeed, the health crisis has further exposed existing inequalities and has accentuated the difficulties of the most disadvantaged and vulnerable people to access adequate and dignified housing, therefore, consolidating the proposed constitutional reform becomes crucial to ensure the dignity of people and protect their fundamental rights.